1983
DOI: 10.1093/oxfordjournals.aje.a113513
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Breast Cancer

Abstract: Since 1976, data were collected to evaluate risk factors for breast cancer in a hospital-based case-control study of 1185 women with breast cancer and 3227 controls. The risk of breast cancer increased with increasing age at first birth; this effect was not accounted for by parity. An early age at first birth appeared to reduce the risk relative to no pregnancy, whereas a late age at first birth was associated with a higher risk than not having a full-term pregnancy. High parity was associated with a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
74
1
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(98 citation statements)
references
References 0 publications
22
74
1
1
Order By: Relevance
“…Besides, there is an advantage of hospital based case-control studies: it is expected that they have similar motivation for answering since both cases and controls are patients in a hospital. In our total sample, the reproductive factors have shown the same pattern as that described in other populations all over the world (Helmrich et al, 1983;Lubin et al, 1982;Ewertz et al, 1990;Talamini et al, 1985;Le et al, 1984;Plesko et al, 1985;Thein-Hlaing et al, 1978;Mirra et al, 1971). However, parity was not found completely in line with what has been generally reported, since have two or three children was associated with a somewhat elevated OR compared with having no child and have more than three children was not significantly associated with a protective effect.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Besides, there is an advantage of hospital based case-control studies: it is expected that they have similar motivation for answering since both cases and controls are patients in a hospital. In our total sample, the reproductive factors have shown the same pattern as that described in other populations all over the world (Helmrich et al, 1983;Lubin et al, 1982;Ewertz et al, 1990;Talamini et al, 1985;Le et al, 1984;Plesko et al, 1985;Thein-Hlaing et al, 1978;Mirra et al, 1971). However, parity was not found completely in line with what has been generally reported, since have two or three children was associated with a somewhat elevated OR compared with having no child and have more than three children was not significantly associated with a protective effect.…”
Section: Discussionsupporting
confidence: 78%
“…There is agreement by most authors on a list of 'established' (Kelsey & Gammon, 1990) risk factors, made up of reproductive and menstrual variables, socioeconomic status, family history of BC and previous benign breast disease. These have been found in most countries where studies have been conducted: North America (Helmrich et al, 1983;Lubin et al, 1987); Scandinavia (reviewed in Ewertz et al, 1990); Western Europe (Talamini et al, 1985;Le et al, 1984); Eastern Europe (Plesko et al, 1985); Asia (Thein & Theen et al, 1978) and South America (Mirra et al, 1971). However, in several studies, there is no risk increase associated with some of these established factors (Adami et al, 1980;East European Study of BC epidemiology, 1990).…”
mentioning
confidence: 91%
“…Several studies have confirmed this, but some found an additional protective effect of high parity (Soini, 1977;Tulinius et al, 1978;Paffenbarger et al, 1980;Brinton et al, 1983;Helmrich et al, 1983;Pathak et al, 1986). Others have failed to demonstrate an association between breast cancer risk and age at first birth (Choi et al, 1978;Thein-Hlaing & Thein-Maung-Myint, 1978;Adami et al, 1980;Pike et al, 1981;Harris et al, 1982;Kvale et al, 1987b).…”
mentioning
confidence: 94%
“…Ever-parous vs nulliparous status, early age at first full-term pregnancy and multiparity have been identified by epidemiological studies as protective against the development of breast carcinoma (MacMahon et al, 1970;Kelsey, 1979;Bain et al, 1981;Lubin et al, 1982;Helmrich et al, 1983). Although the effect of term pregnancy has been extensively evaluated, the mechanism of this protection has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Ever-parous vs nulliparous status, early age at first full-term pregnancy and high total parity are among factors that epidemiological studies have identified as exerting protective effects on breast cancer risk (MacMahon et al, 1970;Kelsey, 1979;Bain et al, 1981;Lubin et al, 1982;Helmrich et al, 1983). The relationship between these reproductive factors and fibrocystic disease is unclear.…”
mentioning
confidence: 99%